Anthology of surreal cinema. - Clair, René 1898-1981; Picabia, Francis 1879-1953; Borlin, Jean 1893-1930; Satie, Erik 1866-1925; Duchamp, Marcel 1887-1968; Ray, Man 1890-1976; Dulac, Germaine 1882-1942; Artaud, Antonin 1896-1948; Allin, Alex; Athanasiou, Génica 1897-1966; Bataille, Lucien; Léger, Fernand 1881-1955; et al. (Cinematheque Francais, 2005)
Entr'acte is an early surrealistic effort based on an idea from painter Frances Picabia. After a man is killed, his coffin takes on a life of its own. After a long surrealistic chase, he climbs out of his coffin and makes everyone that was chasing his coffin disappear.